Effects of Ethanol Lock Therapy on Central Line Infections and Mechanical Problems in Children With Intestinal Failure. (29th January 2016) - Mokha, Jasmeet S.; Davidovics, Zev H.; Samela, Kate; Emerick, Karan
Abstract : Objectives: Although use of 70% ethanol lock therapy (ELT) has been shown to decrease the rate of catheter‐related bloodstream infections (CRBSIs) in patients with intestinal failure and central venous catheters (CVCs), concerns have been raised about its association with higher rates of mechanical problems and CVC replacements (CVC‐Rs). We sought to compare the rates of CRBSI, mechanical problems, and CVC‐Rs in a cohort of pediatric patients with intestinal failure, with and without ELT (ELT + and ELT −, respectively). Methods: Data were collected in a retrospective chart review from February 2007 to May 2014. Mann‐Whitney and Wilcoxon signed‐rank tests were used to compare nonparametric and paired data, respectively. Results: Twenty‐nine children had 9033 catheter days (CDs). The ELT + group (vs ELT − ) had lower rate of infection and significantly fewer CVC‐Rs due to infection but significantly more mechanical events and related CVC‐Rs with significantly shorter mean CVC survival. In 13 children who had a pre‐ELT and post‐ELT period, ELT was associated with a decrease in the rate of CVC‐Rs due to infection (0.36 vs 4.74/1000 CDs, P = .046) and an increase in the rate of CVC‐Rs due to mechanical problems (5.05 vs 0/1000 CDs, P = .018). Conclusions: While ELT + is associated with a lower rate of CRBSIs and related CVC‐Rs, it is also associated with higher rates of mechanical problems and related CVC‐Rs. In addition to investigating the ideal concentration, duration, and timing of ELT to preserve the integrity of the CVC, alternatives to exclusively ethanol‐based lock solutions should be developed.